Costs of Physician Continuous Professional Development: A Systematic Review. (6th July 2022) - Cook, David A.; Wilkinson, John M.; Foo, Jonathan
Abstract : Purpose: An essential yet oft-neglected step in cost evaluations is the selection of resources (ingredients) to include in cost estimates. The ingredients that most influence the cost of physician continuous professional development (CPD) are unknown, as are the relative costs of instructional modalities. This study's purpose was to estimate the costs of cost ingredients and instructional modalities in physician CPD. Method: The authors conducted a systematic review in April 2020, searching MEDLINE, Embase, PsycInfo, and the Cochrane Library for comparative cost evaluations of CPD for practicing physicians. Two reviewers, working independently, screened articles for inclusion and extracted information on costs (converted to 2021 U.S. dollars) for each intervention overall, each ingredient, and each modality. Results: Of 3, 338 eligible studies, 62 were included, enumerating costs for 86 discrete training interventions or instructional modalities. The most frequently reported ingredients were faculty time (25 of 86 interventions), materials (24), administrator/staff time (23), and travel (20). Ingredient costs varied widely, ranging from a per-physician median of 4 for postage (10 interventions) to 525 for learner time (13); equipment (9) and faculty time were also relatively expensive (median > 170). Among instructional modalities (≤ 11 interventions per modality), audit and feedback performed by physician learners, computer-based modules, computer-based virtual patients, in-person lectures, and experiences with real patients were relatively expensive (median > 1, 000 per physician). Mailed paper materials, video clips, and audit and feedback performed by others were relatively inexpensive (median ≤ 62 per physician). Details regarding ingredient selection (10 of 62 studies), quantitation (10), and pricing (26) were reported infrequently. Conclusions: Some ingredients, including time, are more important (i.e., contribute more to total costs) than others and should be prioritized in cost evaluations. Data on the relative costs of instructional modalities are insightful but limited. The methods and reporting of cost valuations merit improvement.